Can profit and loss sharing (PLS) financing instruments reduce the credit risk of Islamic banks? - Shahari, Farihana; Rahman, Md. Saifur (Physica-Verlag GMBH, 2020)
An Islamic bank is an interest-free financial institution that is growing rapidly in both Muslim and non-Muslim countries. It provides loans based on both PLS and non-PLS concepts, where the PLS concept shares both profit and loss with the customers, while the non-PLS concept allows charging a fixed profit rate. The customers are treated as partners who invest either labor or an equal portion of capital. The PLS financing raises an issue of whether the Islamic bank is able to recover the financing amount which is disbursed without any form of collateral. Therefore, this paper explores the possible implication of PLS theory and examines whether the PLS financing instrument reduces the credit risk of Islamic banks. PLS financing is a focus variable, while bank-specific and macroeconomic variables are considered as control variables that enable us to draw a reliable and unbiased result. The study evaluates several hypotheses by employing two-step system GMM estimation technique. It offers several outcomes; PLS financing instrument reduces credit risk. The bank-specific and macroeconomic variables have a mixed effect on credit risk. The study suggests significant policy implications for the Islamic banks for sustaining the competitive banking industries.